Chinese healthy eating index as a measure of diet quality and its association with depression and anxiety symptoms among people living with HIV: a cross-sectional study in China - Tang, Huiling; Nie, Zizheng; Wu, Chenyang; Cheng, Junxia; Zhu, Ke; Liu, Yingying; Zhang, Mu; Wang, Fengying; Han, Shufen (Frontiers in Nutrition, 2026)
AimHigh diet quality has increasingly been acknowledged as a significant factor influencing mental health. This study aimed to investigate the association between the Chinese Healthy Eating Index (CHEI) and mental health issues, specifically depression and anxiety, among people living with human immunodeficiency (PLHIV).Design and methodsIn the cross-sectional study, data were collected from 700 PLHIV through in-person interviews conducted at HIV-specific hospitals in Jinhua city. Dietary intake and food information were obtained using a semi-quantitative food frequency questionnaire, and diet quality was assessed through the CHEI. Depression and anxiety were evaluated using the Hospital Anxiety and Depression Scale (HADS). Multivariate logistic regression models and restricted cubic spline (RCS) analysis were used to examine their associations.ResultsThe average total CHEI scores were 60.8 ± 12.0. After adjusting for potential confounders, participants in the highest quartile of total CHEI scores exhibited a significantly lower likelihood of experiencing symptoms of depression (odds ratio [OR] = 0.35; 95% confidence interval [CI]: 0.20–0.60) and anxiety (OR = 0.57; 95% CI: 0.34–0.96) compared to those in the lowest quartile. The RCS analysis indicated that as total CHEI scores exceeded 60, the risk of experiencing depression and anxiety symptoms showed a declining trend. Furthermore, higher CHEI’s component scores for dark vegetables, fruits, and dairy products were associated with lower odds of experiencing depression and anxiety symptoms within this population.ConclusionOur findings indicated that diet quality, as evaluated by the CHEI, was inversely associated with symptoms of depression and anxiety among PLHIV.